Oxidative balance in brain after chronic exposure to arsenic - Bonetto, Julián Gerardo (2022)
The effect of chronic As exposure in brain, the specific oxidantsproduction and oxidative stress still needs more attention. In the presentstudy, male wistar rats were chronically exposed to As bythe drinkingwater during 60 days. The rats receiving a dose of 10 mg As/l showed a9- and 18-fold increase in the content of As in blood and brain,respectively, as compared to the control group. Histopathologicalchanges were detected in brain samples isolated from animals treatedwith Asas compared to control animals. The oxidation rate of 2ʹ,7ʹ-Dichlorofluorescein diacetate (DCFH-DA) showed no significantchanges after the treatment. A significant increase (13%) in the steadystate concentration of ascorbyl radical (A?) was determined in the brainisolated from animals exposed to 50 mg As/l. The lipid radical (LR?)generation rate and the content of malondialdehyde (MDA) wereincreased by 34% and 32%, respectively in brain isolated from ratsreceiving 50 mg As/l. The content of ascorbate (AH-) in brain was notaffected by the exposure to As.However, the content of glutathione(GSH) and the lipophilic antioxidant α-tocopherol (α-T), weresignificantly decreased after As supplementation, as compared tocontrol brains. The A?/AH- content ratio in rat brain showed no changesassociated to the As supplementation. Nevertheless, a significantincrease of 44% and 55% was determined in the LR?/α-T and MDA/α-Tcontent ratios, respectively, suggesting that the oxidative imbalance inthe lipophilic cellular medium could be the primarily effect of Asassociated to membrane damage.